Pengaruh Kualitas Pelayanan Akademik dan Citra Merek Lembaga terhadap Kepuasan Mahasiswa Universitas Negeri Padang - Susanto, Perengki (Fakultas Ilmu Sosial Universitas Negeri Padang, 2012)
Customer satisfaction is the main purpose of the institution in providing excellent service to customers. Service quality is not only to give customer satisfaction but also to build a good brand image of the institution. This study aims to analyze the influence of academic service quality and the image of institutions on student satisfaction of the State University of Padang (UNP). Population consisted of students enrolled in semester from July to December 2011. Sampling was done by purposive sampling with total sample size of 220 respondents. Data was analyzed with multiple regression analysis. The results showed that: (1) the quality of academic services have a significant effect on the brand image of the institution, (2) the quality of academic services have a significant effect on student satisfaction, (3) the institution's brand image have a significant effect on student satisfaction. Research suggestion for the institution to make continuous improvements of the quality of academic service as a core product in higher education